EDUKASI PAKAN TERNAK BERNUTRISI TINGGI KEPADA PETERNAK KAMBING BERANAK KEMBAR DI DESA OMBE KECAMATAN KEDIRI KABUPATEN LOMBOK BARAT - Harmayani, Ria; Fitriyah, abyadul; Alimuddin, Alimuddin; Mariani, Yuni; Andry Kartika, Ni Made; Andriana Fajri, Nefi; Permadi, Hari; Gunadi, Sahrul; Damar Pamenang, Galang; Aminah Zaim Alyaminy, Ishmah Humaidatul; Nazar Fajri, Lalu Moh. (Bajang Institute, 2024)
The birth of twin goats needs to be prepared and supported by paying attention to the genetic characteristics and environment of the goats, especially the management of animal feed, especially the nutrition of pregnant animal feed, where it is important to increase the quantity and quality of feed. The stages in this service include observation, planning, follow-up and evaluation. The training implementation method is lecture and direct practice, question and answer method and discussion. The results of community service activities in Ombe Baru Village showed that of the 40 goat breeders in Ombe Baru Village, the majority (70% of breeders) were able to select twin and single type goat breeds, were able to improve their feeding management and were able to understand the criteria for high nutritional feed, the concept of feeding according to the needs of the livestock as well as feed requirements to increase the reproduction of goats with twins. It is hoped that breeders will continue to be committed to maintaining the sustainability of twin goat farming, continuing to improve feeding management such as providing superior forages and high nutritional feed, especially for goats with twins.